2019
DOI: 10.3390/en12152843
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Decomposition Analysis of China’s Consumption-Based Greenhouse Gas Emissions

Abstract: The trends of consumption-based emissions in China have a major impact on global greenhouse gas (GHG) emissions. Previous studies have only focused on China's energy-related consumption-based emissions of CO 2 or specific non-CO 2 GHGs without taking overall consumptionbased non-CO 2 GHG emissions into account. Based on a constructed global non-CO 2 GHG emissions database, combined with CO 2 emissions data, this paper fills this gap through an examination and analysis of China's GHG emissions using a global mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Based on these findings in India, the researchers believed that high-expenditure individuals and households need to be more responsible. Haidi Gao et al [57] focused on non-CO 2 GHG emissions, built a global multi-regional input-output (MRIO) model for 2004, 2007, and 2011, and conducted a structural decomposition analysis (SDA) to identify major driving forces in increases in consumption-based emissions. They found that among non-CO 2 GHG emissions, CH 4 , N 2 O, and F gas emissions experienced the fastest growth, although the net exports of non-CO 2 GHG emissions have greatly decreased in recent years.…”
Section: Research Topic Evolution Analysismentioning
confidence: 99%
“…Based on these findings in India, the researchers believed that high-expenditure individuals and households need to be more responsible. Haidi Gao et al [57] focused on non-CO 2 GHG emissions, built a global multi-regional input-output (MRIO) model for 2004, 2007, and 2011, and conducted a structural decomposition analysis (SDA) to identify major driving forces in increases in consumption-based emissions. They found that among non-CO 2 GHG emissions, CH 4 , N 2 O, and F gas emissions experienced the fastest growth, although the net exports of non-CO 2 GHG emissions have greatly decreased in recent years.…”
Section: Research Topic Evolution Analysismentioning
confidence: 99%
“…SDA decomposes the overall change to several component indexes based on the IO table. SDA reveals the change law of each factor in the economic system (Gao et al 2019;Luo et al 2020;Wang and Liu 2021). In this paper, SDA is used to analyse the influence of final demand on pesticide use in different regions in different periods and the direct and indirect factors affecting pesticide use in the process of interconnecting sectors of economic activities.…”
Section: Structural Decomposition Analysis (Sda)mentioning
confidence: 99%
“…A thorough analysis of the literature on the contribution of consumption-based carbon emissions is provided in this section. The recently released work of (Gao et al, 2019;Jijian et al, 2021;Khan et al, 2020;Liobikienė & Butkus, 2019;Macedo et al, 2021;Muhammad & Khan, 2021;Opoku et al, 2021;Sarkodie & Strezov, 2019;Steininger et al, 2018;S. Wang et al, 2017;Y.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CBA is referred to as Consumption-Based Accounting. Some studies use CBA as a sign of GHG (Gao et al, 2019;Khan et al, 2020;Macedo et al, 2021), but the researcher reveals the two apart by declaring them dependent and independent variables. since the data for the two variables are distinct.…”
Section: Milhatun Nisa'mentioning
confidence: 99%